Cobalt Chloride as a Hypoxia Mimicking Agent Induced HIF-1α and mTOR Expressions of Human Umbilical Cord Mesenchymal Stem Cells - Kuntjoro, Mefina; Hendrijantini, Nike; Prasetyo, Eric Priyo; Agustono, Bambang; Sitalaksmi, Ratri Maya; Hendrianto, Eryk; Dinaryanti, Aristika; Rusli, Marvin; Tjendronegoro, Evelyn; Hong, Guang (Pesquisa brasileira em odontopediatria e clínica integrada, 2024)
ABSTRACT Objective: To assess the effects of cobalt chloride (CoCl2) as a hypoxia mimicking agent on human umbilical cord mesenchymal stem cells (hUCMSCs) expression of HIF-1α and mTOR for use in regenerative dentistry. Material and Methods: Human umbilical cord mesenchymal stem cells were isolated and then cultured. The characteristics of stemness were screened and confirmed by flow cytometry. The experiment was conducted on hypoxia (H) and normoxia (N) groups. Each group was divided and incubated into 24-, 48-, and 72-hours observations. Hypoxic treatment was performed using 100 µM CoCl2 on 5th passage cells in a conventional incubator (37°C; 5CO2). Then, immunofluorescence of HIF-1α and mTOR was done. Data was analyzed statistically using One-way ANOVA and Tukey’s HSD. Results: Significant differences were found between normoxic and hypoxic groups on HIF-1α (p=0.015) and mTOR (p=0.000) expressions. The highest HIF-1α expression was found at 48 hours in the hypoxia group, while for mTOR at 24 hours in the hypoxia group. Conclusion: Hypoxia using cobalt chloride was able to increase human umbilical cord mesenchymal stem cells expression of HIF-1α and mTOR.